Clinical study on type 1 tympanoplasty: anatomical and functional outcomes - Kusumanjali, A.; Chaitanya, V. Krishna (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Tympanoplasty is operation to eradicate disease in middle ear and to reconstruct the hearing mechanism. Present study aims at assessment of success rate and hearing improvement following type I tympanoplasty. Methods: 50 patients with chronic suppurative otitis media, tubotympanic type attending department of ENT are taken up for study screened with clinical history and examination. Type I tympanoplasty performed in all patients. Simple mastoidectomy with type I tympanoplasty performed in 8 patients. Patients are followed after surgery on 7th, 14th days and end of 3 months. Anatomical outcome is assessed in terms of graft uptake. Pure tone audiometry was performed at 3 months and air bone gap is considered to assess outcome. Results: Out of 50 cases, 43 cases (86%) showed good success rate by means of graft uptake. Remaining 5 cases showed residual perforation and 3 cases medialization of graft. In 42 patients type1 tympanoplasty is performed, success rate was 80.95% and in cases with where type1 tympanoplasty with cortical Mastoidectomy was done and the success rate was 100%. In the present study mean pre op AB gap was 27.65 dB and mean post op AB gap was 19.07 dB. The difference between the two, i.e., AB gap closure was 8.52 dB which is statistically significant. Conclusions: Type-1 tympanoplasty using temporalis fascia with underlay technique have good surgical success rate with excellent improvement of hearing. Cortical mastoidectomy can be planned depending on the status of the middle ear mucosa.